PENGARUH MEDIA SOSIAL TERHADAP LOYALITAS PELANGGAN PADA RUMAH MAKAN BOTRAM GARUT - Rini Alpiani; Putri Intan Permatasari; Cindi Fatika (Universitas Haji Sumatera Utara, 2024)
Customer loyalty is a customer activity with high repeat purchases and is considered less price sensitive, social media is used to meet between brands and customers with the aim of developing a brand over social media companies may process customers more effectively and cost less in spending. (Supriatna et al., 2022). Sugiyono (2009: 13) quantitative is research to examine certain populations and samples, sampling is done randomly, then analyzed quantitatively or statistically with the aim of testing hypotheses that have been set. The results of the data above, it can be seen that t is 12.553 with a Sig Value, which is 0.000, meaning significantly less than the value of probabilitaz (0.000 0.5) so that it can be concluded that Ho rejected means that social media has a significant influence on Customer Loyalty (H1 received). Because the results are positive, the influence of Social Media on Customer Loyalty is a positive influence. Keywords : Loyality, Media Social.